Quantifying fetal heart health in gestational diabetes: a new approach with fetal heart quantification technology - Zhang, Pengjie; Fu, Xinghui; Zhao, Lijuan; Wang, Lu; Wu, Shuning; Liu, Yanyan; Cheng, Jingliang; Zhang, Shan (Frontiers in Pharmacology, 2024)
Objective: This study aimed to assess the impact of gestational diabetes mellitus (GDM) on fetal heart structure and function using a technique called fetal heart quantification (Fetal HQ),which employs advanced imaging technology for comprehensive analysis.Methods: A total of 180 fetuses with normal heart structures, aged 24 to 40 weeks of gestation, were examined. Four-chamber view (4CV), global sphericity index (GSI), global longitudinal strain (GLS), 24-segment sphericity index (SI), ventricular fractional area change (FAC), cardiac output (CO), and stroke volume (SV) were captured and analyzed using the speckle-tracking technique with Fetal HQ. These parameters were compared between the GDM group and the control group during two gestational periods: 24 +0 to 28 +0 weeks and 28 +1 to 40 +1 weeks. Statistical analysis was performed using independent samples t-tests and Mann-Whitney U tests to identify significant differences.Results: Twenty fetuses from mothers with GDM and 40 from the control group were recruited at 24 +0 to 28 +0 weeks. At 28 +1 to 40 +1 weeks, 40 fetuses from mothers with GDM and 80 from the control group were recruited. The fetal left ventricular global longitudinal function was similar between the GDM and control groups. However, compared to the controls, right ventricular function in the GDM group was lower only at 28 +1 to 40 +1 weeks. In the GDM group, the global sphericity index (GSI) was lower than in the control group at 28 +1 to 40 +1 weeks (1.175 vs. 1.22; p = 0.001). There were significant decreases in ventricular FAC (38.74% vs. 42.83%; p < 0.0001) and 4CV GLS for the right ventricle (-22.27% vs. -26.31%; p = 0.005) at 28 +1 to 40 +1 weeks.Our findings suggest that GDM is associated with decreased right ventricular function in the fetal heart, particularly during the later stages of pregnancy (28 +1 to 40 +1 weeks), compared to fetuses from healthy pregnancies. The Fetal HQ technique represents a valuable tool for evaluating the structure and function of fetal hearts affected by GDM during the advanced stages of pregnancy.